2013
DOI: 10.1111/rssb.12018
|View full text |Cite
|
Sign up to set email alerts
|

Envelopes and Partial Least Squares Regression

Abstract: Summary We build connections between envelopes, a recently proposed context for efficient estimation in multivariate statistics, and multivariate partial least squares (PLS) regression. In particular, we establish an envelope as the nucleus of both univariate and multivariate PLS, which opens the door to pursuing the same goals as PLS but using different envelope estimators. It is argued that a likelihood‐based envelope estimator is less sensitive to the number of PLS components that are selected and that it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
152
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 29 publications
(53 reference statements)
3
152
0
Order By: Relevance
“…We therefore refer to the RRR model as fully supervised. The SupSVD model (2) is also connected with the envelope model that was recently proposed by Cook et al [8] and further developed in [32,7,11,10]. The envelope model is a parsimonious model for multivariate regression that is based on the assumption that variation in the response can be divided into two parts: a material part that is related to the predictor, and ) -an immaterial part that is unrelated to the predictor.…”
Section: Connections With Existing Modelsmentioning
confidence: 99%
“…We therefore refer to the RRR model as fully supervised. The SupSVD model (2) is also connected with the envelope model that was recently proposed by Cook et al [8] and further developed in [32,7,11,10]. The envelope model is a parsimonious model for multivariate regression that is based on the assumption that variation in the response can be divided into two parts: a material part that is related to the predictor, and ) -an immaterial part that is unrelated to the predictor.…”
Section: Connections With Existing Modelsmentioning
confidence: 99%
“…Essentially a form of targeted dimension reduction, this process can lead to substantial efficiency gains when the immaterial variation is large relative to the material variation. Cook, Helland, and Su (2013) adapted envelopes to the predictors, and showed that the SIMPLS algorithm for PLS regression converges to an envelope in the predictor space. Following Cook, Li, and Chiaromonte (2010), they demonstrated that using a likelihood-based objective function to separate the material and immaterial variation and to provide an estimator of the coefficient matrix produces clear and often substantial estimative and predictive advantages over SIMPLS.…”
Section: Introductionmentioning
confidence: 99%
“…We also link the simultaneous envelope method with PLS and CCA. In Section 4, we introduce a likelihood-based objective function that includes the objective functions used by Cook, Li, and Chiaromonte (2010) and Cook, Helland, and Su (2013) as special cases. Novel algorithms for estimating a simultaneous envelope are also given in this section.…”
Section: Introductionmentioning
confidence: 99%
“…LSR plays an important underlying role in many extensions, which can be frequently founded in the literature, e.g., L2 norm regularized LSR (RLSR) [2], locally regularized LSR [3], entropy regularized LSR [4], weighted LSR [5], partial least square regression (PLSR) [6], orthogonal LSR [7], lasso [8], and some recent works including [9][10][11], and [12]. Among them, RLSR and lasso are very popular.…”
Section: Introductionmentioning
confidence: 99%